Pengaruh Model Pembelajaran Problem Based Learning Terhadap Motivasi dan Hasil Belajar Pemeliharaan Baterai pada Siswa Kelas X TKR SMK Negeri 1 Cangkringan Tahun Pelajaran 2018/2019 - Brian Pradana Putra (Universitas Negeri Yogyakarta, 2020)
This quasi-experimental research in education aims to determine the effect of Problem Based Learning models on motivation and learning outcomes of Battery Maintenance in class X TKR, SMK Negeri 1 Cangkringan in the academic year 2018/2019. The data were taken using a questionnaire and tests. The subjects of this study were 64 students consisting of 32 control class students and 32 experimental class students. Hypothesis testing in this study uses t-test between groups. T-test between groups was used to determine differences in learning motivation of the experimental class and control class after being treated, to find out the difference of learning outcomes in experimental class and control class after being given treatment. The results showed that the learning motivation of the experimental class with Problem Based Learning model was higher than the control class with the lecture method and the learning outcomes of the experimental class with the Problem Based Learning model were not higher than the control class with the lecture method on the Battery Maintenance material in class X TKR SMK Negeri 1 Cangkringan, academic year 2018/2019.